La práctica odontológica y la subjetividad - Cortes-Castaño, Nelson (Revista Facultad de Odontología Universidad de Antioquia, 2020)
The Health Practice in Dentistry is different from the Dental Practice; the last one, becomes reality during the instrumented action in the oral cavity. The Dental Practice favors the separation between the subject that knows and the object to be known, in other words, it makes the reality an object. On the contrary, the Health Practice in Dentistry promotes the link between subjects —the intersubjectivity— because it is a relationship by words. With the Health Practice in Dentistry the ethic-subject is established, with whom it is possible to create a social tie —the relationship with the other one's word— all of that in function of an ethics that make us responsible of words and actions.